Paediatric optometry AHOV3214 lab book - Ahmad, Norsham; Abdul Rahim, Muhammad Afzam Shah (2021)
The first version of the Paediatric Optometry lab book was created in 2014 and I did some amendment every year to ensure the LOs of the course is achieved. The final version was amended in 2020. This lab book is a compilation of lab manuals and questions used in the Paediatric Optometry course. Paediatric Optometry is a core course for the Optometry programme offered in year 2, semester 1.